2021
DOI: 10.1302/2058-5241.6.200105
|View full text |Cite
|
Sign up to set email alerts
|

A structured evaluation of the symptomatic medial Oxford unicompartmental knee arthroplasty (UKA)

Abstract: Unicompartmental knee arthroplasty (UKA) has several advantages over total knee arthroplasty; however, in many reports, the risk of revision remains higher after UKA. Many reasons for failure of UKA exist. Successful treatment starts with accurate assessment of the symptomatic UKA as a specific mode of failure requires a specific solution. A structured and comprehensive evaluation aids assessment of the symptomatic UKA. This review provides an overview of the causes for a symptomatic medial UKA, its risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Common causes for bearing failure following UKA comprise malpositioning of the component, inadequate size of the insert, residual ligamental laxity, knee deformities or wear. 4 Traumatic injuries can lead to bearing dislocation or in rare cases, to breakage of the component. In a report by Lim et al., a worn Oxford III meniscal bearing fractured 7 years after primary surgery as a result of significant wear and was replaced with a thicker bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Common causes for bearing failure following UKA comprise malpositioning of the component, inadequate size of the insert, residual ligamental laxity, knee deformities or wear. 4 Traumatic injuries can lead to bearing dislocation or in rare cases, to breakage of the component. In a report by Lim et al., a worn Oxford III meniscal bearing fractured 7 years after primary surgery as a result of significant wear and was replaced with a thicker bearing.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons aim to use thin bearings (either 3.5 mm-Size 3 or 4.5 mm-Size 4) with the OUKR to make a conservative tibial resection. Despite the use of thin bearings wear is a rare cause of failure for the OUKR [1]. Excessive linear wear can result in bearing fracture in the long-term, however this complication can easily be treated by inserting a new bearing [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…4 Knee alignment after UKA is critical to prevent complications such as KOA progression and early loosening and is a determinant of UKA longevity. [5][6][7] Postoperative knee alignment is also the most important factor that the surgeon can control and modify. A number of studies have demonstrated the correlation between postoperative knee alignment and clinical outcomes and UKA survival.…”
Section: Introductionmentioning
confidence: 99%
“…Knee alignment after UKA is critical to prevent complications such as KOA progression and early loosening and is a determinant of UKA longevity 5–7 . Postoperative knee alignment is also the most important factor that the surgeon can control and modify.…”
Section: Introductionmentioning
confidence: 99%